Effects of tobacco smoke inhalation on the morphology and cell proliferation rate in Wistar rats submandibular glands (Research, Society and Development, 2021)
Cigarette smoke compromises the salivary glands, altering saliva. Cotinine is the most effective biomarker to assess tobacco consumption, and passive smokers are characterized by serum cotinine levels above 2.1 ng/mL. This study aimed to evaluate the effect of exposure to cigarette smoke on rats submandibular glands. The morphology, the proliferative cells of intercalated ducts (immunohistochemistry for KI-67) and its correlation with serum cotinine levels were analyzed. Wistar rats were grouped: control (C); inhalation of smoke for 30 days (T1) and 60 days (T2). Data were analyzed with the Levene variance homogeneity test, Spearman's test, ANOVA and Tukey's post-test, with significance p